2015
DOI: 10.1111/clr.12555
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgical treatment of crestal bone: quantitative comparison of post‐extractive socket outcomes with those of traditional treatment

Abstract: With both thin and thick buccal plates, the piezosurgical extraction technique of teeth significantly decreases the horizontal resorption of the hard tissue ridge, but not the vertical resorption. Moreover, buccal plate thickness seems to be a key factor in post-extractive bone resorption: the thinner the buccal plate the greater the horizontal crestal bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, all of these options are associated with significant rate of complications, increased morbidity, high costs, and prolonged time of therapy [ 11 13 ]. In the attempt to reduce the need for advanced surgical procedures and to simplify the treatment plan, specific surgical techniques were developed to reduce postextractive ridge resorption [ 14 , 15 ]. Alveolar ridge preservation (ARP), with the application of different biomaterials, is the most common procedure aiming to control crestal bone resorption following dental extractions [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, all of these options are associated with significant rate of complications, increased morbidity, high costs, and prolonged time of therapy [ 11 13 ]. In the attempt to reduce the need for advanced surgical procedures and to simplify the treatment plan, specific surgical techniques were developed to reduce postextractive ridge resorption [ 14 , 15 ]. Alveolar ridge preservation (ARP), with the application of different biomaterials, is the most common procedure aiming to control crestal bone resorption following dental extractions [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Bone healing probably related to various factors including searching methods, the size of the bone defect, and timing in histopathological examination. 23,24 Furthermore, Gomes et al, 13 in their study on animals found that healing was delayed as shown by histological follow-up, in the group that used only the hAM. The reason for higher bone building levels in the conventional surgery on 21 st day likely that the hAM maintains its tissue integrity by performing its barrier function in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Complicated extractions, such as the removal of ankylosed and endodontically treated teeth, can cause excessive bleeding, if the surgical procedures of flapping and deboning are conducted [5,6]. Given that such aggressive procedures may further increase the bleeding risk in DAPT patients, the flapless approach serves as an ideal alternative owing to its less traumatic nature, and turbine handpieces (TH) with burs specially designed to create dento-alveolar spaces are commonly used instruments [7,8]. Although the cutting action of TH is highly efficient, the rotating working mode of the bur and the high operational pressure limit the cutting precision and intraoperative control, thereby causing unwanted adjacent tissue injuries and subsequent prolongation of intra-alveolar clotting [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Given that such aggressive procedures may further increase the bleeding risk in DAPT patients, the flapless approach serves as an ideal alternative owing to its less traumatic nature, and turbine handpieces (TH) with burs specially designed to create dento-alveolar spaces are commonly used instruments [7,8]. Although the cutting action of TH is highly efficient, the rotating working mode of the bur and the high operational pressure limit the cutting precision and intraoperative control, thereby causing unwanted adjacent tissue injuries and subsequent prolongation of intra-alveolar clotting [7,9]. It is worth noting that, although the flapless extraction using TH (FET) is less invasive, the rough cutting characteristic of the instrument may amplify the adverse effect of DAPT on the post-extraction clotting process [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation